Ketogenic parenteral nutrition in 17 pediatric patients with epilepsy. Issue 1 (16th November 2017) - Dressler, Anastasia; Haiden, Nadja; Trimmel‐Schwahofer, Petra; Benninger, Franz; Samueli, Sharon; Gröppel, Gudrun; Spatzierer, Sina; Mühlebner, Angelika; Abraham, Klaus; Feucht, Martha
Summary: Objective: Ketogenic parenteral nutrition (kPN) is indicated when enteral intake is temporarily limited or impossible, but evidence‐based prescriptions are lacking. Objective was to evaluate the efficacy and safety of kPN in children with epileptic encephalopathies using a new computer‐based algorithm for accurate component calculating. Methods: Children with epilepsy receiving kPN were included. A computer‐based algorithm was established on the basis of guidelines of the European Society for Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN): fat intake not exceeding 4 g/kg/day, age‐adequate supply of protein, electrolytes, vitamins, and trace elements, but reduced carbohydrates. Primary outcome was successfully reaching relevant ketosis, defined as beta‐hydroxybutyrate plasma level of ≥ 2 mmol/L. Efficacy was defined as seizure reduction ≥50% in de novo kPN and maintenance of response in children already on a ketogenic diet (KD). Safety was assessed by adverse effects, laboratory findings, and the appropriateness of nutritional intake. Results: Seventeen children (median 1.84 years) were studied, of which 76% (13/17) were already on an oral ketogenic diet. Indications for kPN were surgery, status epilepticus, vomiting, food refusal, and introduction of enteral feeding in neonates. The parenteral fat/nonfat ratio was mean 0.9 (±0.3; range 0.6–1.5). Relevant ketosis was reached in 10 children (median 2.9 mmol/L), but not in 7 (median = 1.4 mmol/L). In de novo kPN, significant response was observed in 50% (2/4); in patients previously responding to the KD (77%, 10/13), response was maintained. A significant correlation between the degree of ketosis and seizure reduction (correlation coefficient = 0.691; p = .002) was observed. Only mild and transient adverse events occurred during kPN. Significance: KPN with fat intake of 3.5–4.0 g/kg/day was safe and effective. KPN was tailored according to guidelines and individual nutritional needs. In nearly half of the patients, ketosis was lower than during oral KD. Despite this, seizures remained controlled.